Abnormal loan growth and bank risk-taking in Vietnam: A quantile regression approach - Tin H. Ho; Tu D. Q. Le; Dat T. Nguyen (Cogent Business & Management, 2021)
We empirically investigate and present evidence of nonlinearity and heterogeneity in the impact of abnormal loan growth on risk-taking in the Vietnamese banking system between 2007 and 2019, using a quantile regression method. Our results showed that abnormal loan growth initially helped banks to reduce risk-taking. However, this relationship was U-shaped and heterogeneous. The effect of abnormal loan growth was more significant for banks at the upper tail of the risk-taking distribution. Our findings also demonstrated that the turning point of abnormal loan growth increased throughout the risk-taking distribution. Hence, our findings suggest that the pursuit of excessive lending is more likely to result in greater bank risk-taking.
Keywords: G21; G32; 650; abnormal loan growth; bank risk-taking; Vietnam; quantile regression; nonlinearity